Transport and Mixing Dynamics on Coastal Phytoplankton Patches during Summer Breeze Season - R. Martellucci; A. Pierattini; F. Paladini de Mendoza (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
Coupling between sea/land breeze and coastal circulation and the influence of wind-driven dynamics are substantially relevant for understanding coastal Mediterranean ecosystems. These coastal areas are particularly dynamic and are characterized by high-variable processes which drive biological phenomena at different time-scale. Hydrodynamic studies on coastal water circulation and their influence on primary producers are limited, this is especially true for the Tyrrhenian sea in which available information on coastal dynamics is confined to large-scale general circulation with a focus exclusively on mesoscale pelagic dynamical processes. During the periods of fair weather, especially in the summer season, Tyrrhenian coastal waters are dominated by daily patterns of local breeze circulation. These winds induce coastal current and buoyancy-derived motions modulating the coastal phytoplankton patches. About 30% of the Italian population lives at the land-sea transition zone, during the summer season recreational activity increases the population in these coastal areas increasing the human pressure on the coastal systems. As a consequence, it is necessary to better understand the coastal processes significant for environmental and navigational interests. This paper presents physical and biological data to document the effect of sea/land breeze circulation on current dynamics and water column structures in a Northern Tyrrhenian coastal site. The in situ data show that coastal currents are predominantly controlled by tide and local wind and respond rapidly to changes in wind direction. Water column thermal structure analyses reveal significant changes with the morning’s rotation of breeze: lifting of isotherms (cooling) was typically observed in deep layers during early mornings, accompanied by fluctuations in isotherms.